From Debate to Dialogue: Cultivating Intercultural Citizenship through Critical Thinking in Indonesian EFL Classrooms - Feby Febriyani Purba; Suci Rohani; Syakira Ramadhani; Ratna Andhika Mahaputri; Siti Aisyah (Publikasi Indonesia, 2025)
The integration of Intercultural Communication Pedagogy (ICP) into English as a Foreign Language (EFL) instruction plays a vital role in fostering not only linguistic and cultural understanding, but also the development of intercultural citizenship. In the Indonesian higher education context, the incorporation of ICP in courses that emphasize Critical Thinking (CT) and English Debate (ED) remains limited. However, these components hold significant potential for preparing learners to become active, reflective, and engaged citizens in a globalized world. This study aims to explore how CT and ED are taught in an Indonesian EFL classroom through the lens of ICP, with a particular focus on how these practices contribute to the formation of intercultural citizenship. Employing a survey-based approach, data will be collected through document analysis (syllabi and lesson plans), questionnaires, and interviews. Participants will include twenty-one student teachers and one course instructor. The analysis will be guided by the Intercultural Communicative Competence (ICC) framework—comprising knowledge, attitude, and skills—to examine how instructional strategies support students in developing the critical awareness, empathy, and responsibility essential to intercultural citizenship. The study is expected to offer practical insights into how EFL pedagogy can move beyond language proficiency to foster a sense of global responsibility and active participation across cultures.